PENGELOLAAN GULMA KEDELAI MELALUI VARIAN DOSIS MULSA ORGANIK KIRINYUH (Chromolaena odorata L) DAN HERBISIDA OXYFLUORFEN - Ramut, Anuar; Untari, Yulis; Ainun, Cici; S, Taupiq; Pratama, Ferdy; Ardiansyah, Ardiansyah (AGRICA, 2025)
A popular practice for weed management in soybean cultivation is the use of Siam weed (Chromolaena odorata L.) organic mulch and oxyfluorfen herbicide. This study aimed to determine the appropriate dose of Siam weed mulch and oxyfluorfen for effective weed suppression, improved growth, and yield of soybean. The experiment was conducted from July to September 2025 in Lawe Sagu Hulu Village, Lawe Bulan Subdistrict, Aceh Tenggara, Aceh, Indonesia. A non-factorial randomized block design (RBD) was employed with 12 treatments; D0:control; D1:12.5 organic mulch; D2:14.0; D3:15.5; D4:17.0; D5:18.5 t ha?¹; D6:300 oxyfluorfen herbicide; D7:500;  D8:700; D9:900; D10:1100 g a.i. ha?¹; and D11:continuous mechanical control, replicated four times. Experimental plots measured 2.5 × 2.5 m, with Siam weed mulch applied as 10 cm chopped biomass spread evenly on the soil surface, while oxyfluorfen was applied at 1 DAS. Observed variables included weed cover percentage, plant height, number of pods, and 100-seed weight. Results showed that Siam weed mulch at 17 t ha?¹ significantly increased soybean height at 20 and 30 DAS. Oxyfluorfen at 900 g a.i. Ha-¹ effectively reduced weed cover and decreased the number of pods per plant.